PREDIKSI PERKEMBANGAN LAHAN PERMUKIMAN TERHADAP KERENTANAN BENCANA BANJIR DAN KEBAKARAN DI PERMUKIMAN TEPIAN SUNGAI KAPUAS KOTA PONTIANAK - Ely Nurhidayati; Imam Buchori; Mussadun Mussadun (TATALOKA, 2016)
Settlements of house on stilts in the Eastern Pontianak is located at the triangle of the Kapuas River and Landak River. This study to determine the changes of settlement’s areas in 2003-2014, predict the settlement’s areas in 2020 and the correlation between the disaster vulnerability and the development of settlement’s areas in the Kapuas riverbanks. This research method integrates quantitative-SIG binary logistic regression and CA-Markov. The data used are Quickbird satellite imagery (2003), elevation data ICONOS (2008) and contour intervals (1 meter). The results are the prediction accuracy (79.74%) and the highest kappa index (0.55). The prediction of settlement’s areas (481.98 hectares) in 2020, shows the highest land expansion in the Parit Mayor Village and the increase of settlement’s areas (6.80 ha/year) in 2014-2020. Regression analysis have a coefficient of 0 in the flooding variable, so the floods did not affected the development of settlement’s areas in the Eastern Pontianak.